Melanosis coli in patients with colon cancer - Dorota Biernacka-Wawrzonek; Michał Stępka; Alicja Tomaszewska; Agnieszka Ehrmann-Jóśko; Natalia Chojnowska; Magdalena Zemlak; Jacek Muszyński (Gastroenterology Review)
Intoduction: Melanosis coli is a benign lesion affecting the mucosa of the large intestine. There is a relationship between the presence of melanosis and anthraquinone laxative use. Melanosis coli is also observed in patients with colon cancer, but there is doubt whether these two conditions are related. Aim : To analyze the correlation between melanosis and colon cancer. Material and methods: We analyzed retrospectively 436 patients undergoing colon cancer surgery. There were 246 women and 190 men. Patients were divided into three age groups: under 50 years, between 51 and 65 years, and over 66 years. We analyzed sections of the cancer and intestinal mucosa from the tumor’s proximal (2–5 cm) and distal (8–10 cm) zone. Results : Melanosis coli was present in 52 patients, which represents 11.9% of patients with colon cancer. More often it was present in women. The most common location of melanosis and colon cancer was the terminal part of the large intestine. In patients below 50 years of age in both sexes melanosis coli did not occur. In men, melanosis was more common in the age group over 66 years. Intensity of pigmentation was higher in the tumor’s distal zone. Conclusions : The incidence of melanosis coli increases with age, similar to that of colon cancer. Melanosis was not present inside tumors, in almost half of the cases it was not present in the proximal zone, and the degree of pigmentation increased in distal zone. The cause-effect relationship between melanosis coli and colon cancer remains uncertain.